Republic of Turkey (Washington, D.C.)
7 mikrofiş (1. mikrofiş (49 poz) ; 2. mikrofiş (49 poz) ; 3 mikrofiş (49 poz) ; 4. mikrofiş (49 poz) ; 5. mikrofiş (49 poz) ; 6. mikrofiş (49 poz) ; 7. mikrofiş (21 poz))